(untitled) (Vietnam Journal of Community Medicine, 2026)
Lung cancer associated with cystic airspaces (LC-CAS) represents an uncommon and often underrecognized presentation of lung adenocarcinoma in which tumor growth occurs within or along the wall of a pre-existing cystic airspace, including emphysematous bullae. Because these lesions may appear as thin-walled benign structures on CT and may lack fluorodeoxyglucose (FDG) uptake on PET/CT, they pose a significant diagnostic challenge. We describe a rare case of synchronous primary lung adenocarcinomas in a 75-year-old man: a PET-avid solid mass in the left lower lobe and a second PET-negative invasive adenocarcinoma arising along the wall of an apical pulmonary bulla in the left upper lobe. Despite its benign radiologic appearance and absence of metabolic activity, histopathology confirmed the presence of invasive malignancy. This case highlights that PET negativity does not reliably exclude malignancy in cystic lung lesions and underscores the necessity of meticulous CT evaluation and multidisciplinary correlation to prevent delayed or missed diagnosis.